Parent-bias - Guilherme Lichand; Juliette Thibaud (University of Zurich, Department of Economics, 2020)
This paper uses a lab-in-the-field experiment in Malawi to document two new facts about how parents share resources with their children over time. First, for almost a third of study participants, the further in the future consumption is, the more generous are parents' plans to share it with their children. Second, many participants revise those plans as consumption gets closer, reallocating from children towards themselves - even when consumption is still in the future. None of these patterns can be accounted for by present-bias. Instead, both are consistent with a relevant share of parents discounting their future utility of consumption to a greater extent than that of their children. We document that parents characterized by such asymmetric geometric discounting display sizable preference reversals every period, a phenomenon we denote parent-bias. We find that, despite ambitious plans, those parents actually allocate less to their children in the present than other parents, and that such preferences predict under-investment in children outside the lab just as much as quasi-hyperbolic discounting. Commitment devices designed for present-bias do not mitigate parentbias. Our findings provide a new explanation for under-investment in children and inform the design of new interventions to address it.
Keywords: C91; D13; E24; 330; Time preferences; Preference reversals; Children's human capital